Evaluating the role of PLGF and VEGFR-1/ Flt-1 in the development of cervical intraepithelial neoplasia and invasive cervical carcinoma in the background of HIV infection in women living in South Africa - Walters, Tasha-Leigh (Stellenbosch : Stellenbosch University, 2026)
Thesis (M in Pathology)--Stellenbosch University, 2026.